PENGARUH KETEPATAN WAKTU DAN SHIPMENT TRACKING TERHADAP KEPUASAN PELAYANAN PADA PELANGGAN JNE NUSA INDAH KOTA BENGKULU - Ambystisela, Agdtia; Subandrio, Subandrio (Yayasan Insani Mandiri Santani, 2024)
This study aims to determine the influence of Punctuality and Shipment Tracking on Service Satisfaction in JNE Nusa Indah Bengkulu City Customers. This type of research uses a quantitative descriptive research method. The population used in this study is customers from JNE Bengkulu City. The number of respondents in this study is 100 people. The data collection method uses a questionnaire and uses analysis techniques using multiple linear regression analysis tests and hypothesis tests, namely t-test and f-test. Based on the results of multiple linear regression, the form of the regression equation Y = 4.096 + 0.255 (X1) + 0.451 (X2) and the results of the t test and f test of this study can be concluded that Timeliness has a significant effect on service satisfaction, this is evidenced by the results of the t test showing > values (4.144 > 1.984) and (sig α = 0.00 < 0.050). This means being rejected and accepted. Shipment tracking has a significant effect on service satisfaction, this is evidenced by the results of the t-test showing > values (8.935 > 1.984) and (sig α = 0.00 < 0.050). This means being rejected and accepted. Punctuality () and Shipment tracking () together have a significant effect on service satisfaction (Y) in JNE Nusa Indah Kota Bengkulu customers, this is evidenced by the F test showing a value of >, namely (177,291 > 2.70) and (sig α = 0.000 < 0.050),. This means being rejected and accepted.t_hit t_tabel H_0 H_a t_hit t_tabel H_0 H_a X_1 X_2 F_hitung F_tabel H_0 H_aKeywords: Punctuality, Shipment Tracking, dan Kepuasan Pelayanan